MENINGKATKAN DAYA SAING PRODUK MELALUI EFISIENSI PRODUKSI DAN PEMASARAN DIGITAL PADA PENGRAJIN KULIT - Dyahjatmayanti, Dhiani (Dharma: Jurnal Pengabdian Masyarakat, 2024)
Yanto Leather is one of the leather craftsmen at the Manding Craft Industry Center, Bantul Regency, Special Region of Yogyakarta. Since the Covid-19 outbreak attacked Indonesia in March 2020, it has had an impact on the MSME sector, including the Manding Leather Crafts Industrial Center. The impact felt most by leather craftsmen was the decline in sales turnover during the pandemic, including Yanto Leather. The aim of the activity is to improve the skills of Yanto Leather craftsmen in production efficiency and digital marketing. The methods used are coordination and collaboration with partners, training and mentoring. The output of this program includes increasing the application of science and technology where craftsmen are able to use social media for digital marketing, a new brand called Yanto Hastkala, and a product catalog that has been registered for copyright, and the provision of leather sewing machines to increase production efficiency.